Acute Limb Ischemia and Pseudoaneurysm of Femoralis Artery Post Cardiac Catheterization in Pediatric - Perdana H. &; Kurnianingsih N. (ACI (Acta Cardiologia Indonesiana), 2017)
Acute Limb Ischemia and Pseudoaneurysm of Femoralis Artery Post CardiacCatheterization in Pediatric